INFORMATION AND COMMUNICATION TECHNOLOGIES OF LEARNING AND THEIR APPLICATION IN THE MODERN EDUCATIONAL PROCESS (ІННОВАЦІЙНІ ПРОЦЕСИ ОСВІТНЬОЇ СФЕРИ УКРАЇНИ ТА КРАЇН ЦЕНТРАЛЬНОЇ ЄВРОПИ: СТАН, ПРОБЛЕМИ І ПЕРСПЕКТИВИ, 2024)
.